Eminescu and Kabbalah - Cojocaru, Andrei Victor (Swedish Journal of Romanian Studies, 2024)
In the pages of this article, we will bring together a series of interpretations of Eminescu’s writings that prove the influence of the mysticism of Kabbalah on the great Romanian author. The understanding of Eminescu’s poems through the lens of Kabbalah is a perspective adopted by several scholars. For example, starting with G. Călinescu, Hyperion (from the poem “Luceafărul”) was compared to a sefirah. Since the influences of the Far East seem to be much more significant in the literary context in question, we will start from them and, later, correlate them with elements from the ideological background of Near Eastern mysticism. We will also point out certain aspects of the symbolism of the elements and, above all, of water – which is, ultimately, an emblem of the primordial space from which existence is born. Thus, starting from the perspective of Gaston Bachelard’s poetics of the elements, we will investigate the correlation with the mysterious Ain Soph of Kabbalah.